Progress of rituximab in the treatment of systemic lupus erythematosus and lupus nephritis - Mo, Shouqi; Li, Yilan; He, Junbing; Lin, Ling (Frontiers in Medicine, 2024)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with heterogeneous clinical manifestations, often leading to significant morbidity and mortality, particularly due to lupus nephritis (LN). The standard therapeutic approach involving mycophenolate mofetil, cyclophosphamide, and glucocorticoids has shown limitations due to cumulative toxicity and side effects. The introduction of biologic agents, especially rituximab (RTX), a chimeric monoclonal antibody targeting CD20+ B cells, has revolutionized the treatment landscape. This review synthesized the current understanding of B cells' role in SLE and LN and evaluates RTX's therapeutic impact. B cells contribute to disease pathogenesis through autoantibody production and immune complex formation, leading to tissue damage. RTX's mechanisms of action, including Complement-Dependent cytotoxicity (CDC), antibody-dependent cellmediated cytotoxicity (ADCC), and induction of apoptosis, have demonstrated efficacy in both SLE and LN treatment. Clinical studies have reported remission rates and improved renal outcomes with RTX use, although challenges such as human antichimeric antibody development and optimal dosing persist. The review emphasized the need for continued research to elucidate RTX's long-term benefits and risks, and to explore personalized treatment strategies that incorporate B cell biology for better disease management in SLE and LN.